Current Understanding of Androgen Signaling in Prostatitis and its Treatment: A Review - Cabeza, Marisa (Current Medicinal Chemistry, 2024)
Chronic prostatitis is a highly prevalent condition that significantly impacts the quality of life and fertility of men. Because of its heterogeneous nature, there is no definitive treatment, which requires ongoing research into its etiology. Additionally, the association between prostatitis and an elevated risk of prostate cancer highlights the importance of comprehending androgen involvement in prostatitis. This paper examines the current understanding of androgen signaling in prostatitis and explores contemporary therapeutic approaches. It was reviewed Medline articles comprehensively, using keywords such as nonbacterial prostatitis, prostatitis infertility, androgen role in prostatitis, and chronic pelvic pain. Several cellular targets are linked to androgen signaling. Notably, the major tyrosine phosphatase activity (cPAcP) in normal human prostate is influenced by androgen signaling, and its serum levels inversely correlate with prostate cancer progression. Androgens also regulate membrane-associated zinc and pyruvate transporters transduction in prostate cells, suggesting promising avenues for novel drug development aimed at inhibiting these molecules to reduce cancer tumor growth. Various therapies for prostatitis have been evaluated, including antibiotics, anti-inflammatory medications (including bioflavonoids), neuromodulators, alpha-blockers, 5α-reductase inhibitors, and androgen receptor antagonists. These therapies have demonstrated varying degrees of success in ameliorating symptoms.In conclusion, aging decreases circulating T and intraprostatic DHT, altering the proper functioning of the prostate, reducing the ability of androgens to maintain normal Zn2+ levels, and diminishing the secretion of citrate, PAcP, and other proteins into the prostatic fluid. The Zn2+-transporter decreases or is absent in prostate cancer, so the pyruvate transporter activates. Consequently, the cell ATP increases, inducing tumor growth.
Keywords: Prostate diseases